(untitled) (Journal of the College of Basic Education, 2025)
The research aims to reveal the effectiveness of the strategy (Do-Review-Study-Apply) in the mental skills for second-year middle school female students in physics. The null hypothesis was derived, which states: “There is no statistically significant difference at a significance level of (0.05) between the average scores of the experimental group students who will study physics according to the (Do-Review-Study-Apply) strategy and the average scores of the control group students who study the same subject according to the usual method in the mental skills test.” The experimental design was adopted with partial control for two equal groups. To achieve the research objective, a random sample of (76) female students was selected from “Martyr Adel Nasser Secondary School” affiliated with Karbala Education Directorate. They were distributed into two groups: the experimental group (39) female students and the control group (37) female students, for the first semester of the academic year (2024-2025). The study material was represented by the first three chapters of the Physics book - Second Intermediate, which included (14) skills. On this basis, two mental skills tests were prepared, consisting of (28) items, and their validity and reliability were verified. The following statistical methods were used: (Kuder-Richard-20 equation, the coefficient of ease, difficulty, discrimination, effectiveness of false alternatives, Pearson’s correlation coefficient, t-test for two independent samples, and chi-square) to verify the research results. After applying the research tool to the research sample, the results revealed that the experimental group outperformed the control group in the (mental skills test). Based on this, conclusions, recommendations, and proposals were presented.